Detection of a Low Level and Heterogeneous B Cell Immune Response in Peripheral Blood of Acute Borreliosis Patients With High Throughput Sequencing - Kirpach, Josiane; Colone, Alessia; Bürckert, Jean-Philippe; Faison, William J.; Dubois, Axel R. S. X.; Sinner, Regina; Reye, Anna L.; Muller, Claude P. (Frontiers in Immunology, 2019)
The diagnosis of acute Lyme disease is not straightforward. Therefore it is important to develop new strategies to improve diagnostic processes. Detailed analysis of patients’ B cell repertoires by High Throughput Sequencing (HTS) revealed antigen-associated “signatures” which have a huge potential to support diagnosis of acute infections. The human B cell immune response to Borrelia burgdorferi – the causative agent of Lyme disease – has mainly been studied at the antibody level, while less attention has been given to the cellular part of the humoral immune response. There are indications that Borrelia actively influence the B cell immune response and that it is therefore not directly comparable to responses induced by other infections. The main goal of this study was to identify B cell features that could be usable to support diagnosis of acute Lyme disease. For that, we characterized the B cell immune response in acute Lyme disease patients by combining multicolor flow cytometry, single Borrelia reactive B cell isolation and B cell repertoire deep sequencing. Our phenotyping experiments showed, that there is no substantial change at the B cell subpopulation level that would allow to distinguish acute Lyme disease from controls. B cell receptor sequences from individual epitope-reactive B cells had little in common between each other. HTS showed however a higher complementarity determining region 3 (CDR3) amino acid (aa) sequence overlap between samples from different timepoints in acute patients as compared to controls. This indicates, that HTS is sensitive enough to detect ongoing B cell immune responses in these patients. Although each individuals’ repertoire was predominated by rather unique clones, clustering of bulk B cell repertoire sequences revealed a higher overlap of IgG B cell repertoire sequences between acute patients as compared to the controls. These results indicate, that a set of Borrelia-specific B cell repertoire sequences could indeed function as signature to support the diagnosis of acute Lyme disease. The present study is a first step towards the understanding of how information from B cell repertoires might be useful for this purpose.